Development of D-PATH website on diet and physical activity to manage hypertension for Malay population / Mohd Ramadan Ab Hamid - Ab Hamid, Mohd Ramadan (2023)
Controlling blood pressure in hypertensive patients requires continuous education on diet and physical activity management. Many available websites on hypertension were average in quality and missing of integration of behavioural change theories, learning and multimedia theories. This study aims to develop D-PATH website on diet and physical activity to manage hypertension for Malay population. The development process involves three phases: 1) needs assessment, 2) design, development, and evaluation and 3) feasibility study. To achieve the objectives, a mixed-method approach was employed. Phase I explored the web components and content of a web-based nutrition education intervention module for hypertension based on patient preferences, a review of the literature, and an analysis of clinical guidelines for hypertension. As suggested by 14 hypertensive patients, the website should include an overview of hypertension, diet, and physical activity, and use a variety of multimedia components in line with the literature review and clinical guidelines. Phase II was aimed at designing, developing and evaluating the website in which a module on diet and physical activity was developed to be used for the website. The theories of behavioural change, multimedia, and instructional design were also used as the basis for the website. The website was quantitatively tested for validity and acceptability by 13 experts from the fields of dietetics, medicine, and clinical psychology. The content of the website is valid, and the experts agreed that the website can be used for education intervention among hypertensive patients. In Phase III, the website was evaluated to determine its feasibility for the intervention and to identify any necessary revisions. The feasibility study lasted 4 weeks and included 38 patients at baseline, but only 18 completed the study. The website was rated as highly understandable and actionable (score > 90%). Participants were satisfied with the website and there was a positive improvement in knowledge, attitude, and practice. Physical activity levels also improved with the participants being moderately to vigorously active at the end of the study. However, no changes were observed in dietary intake, blood pressure, and anthropometric measurements. In conclusion, D-PATH website is capable in improving the knowledge, attitude, and practice but no changes were observed in patients’ behaviour before and after intervention. The website could also be adopted for an intervention study with a larger number of patients and serve as a reference for healthcare providers to develop an educational website. The development of the D- PATH website adds value to the healthcare system as it can be used as an additional tool for nutrition education. The novelty of this study is the process of designing and developing the website using the behavioural change theory, learning and multimedia theories, and instructional design, along with the concept of edutainment being integrated into the content of the website.